Sosialisasi Pentingnya Pendidikan Anak Usia Dini dalam Mengembangkan Potensi yang Dimiliki Anak di Desa Binuni, Kecamatan Bolangitang Timur, Kabupaten Bolaang Mongondow Utara, Provinsi Sulawesi Utara - Nunung Suryana Jamin; Icam Sutisna; Sri Wahyuningsi Laiya; Rapi Us. Djuko; Fitriah Suryani Jamin; Sulastya Ningsih; Astri Latarima (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service activity aims to socialize the importance of early childhood education in developing children's potential. In carrying out this community service activity, the lecture method is used, namely through the technique of presenting socialization material, which was followed by a question and answer discussion between the presenters/resources and the participants. The low level of public awareness in participating in early childhood education services is due to a lack of information and heavy economic conditions/burden which means that early education is not a top priority for the community compared to food and clothing needs. This socialization activity needs to be carried out on an ongoing basis by involving various related parties (stakeholders), including the village government, mothers and PKK cadres, parents of children, the private sector and campuses so that they receive financial support, personnel and human resources to support carrying out similar activities. in the future. The implementation of socialization activities began with the presentation of the first speaker, then continued with the presentation of the second speaker and ended with a question and answer session for participants and presenters. This activity produces additional information for participants in the form of knowledge and understanding about the importance of early childhood education in developing children's potential. With this additional information, it is hoped that public awareness will increase in involving their children in early childhood education services.